2023
DOI: 10.1039/d3py00773a
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides with low dielectric constants and dissipation factors at high frequency derived from novel aromatic diamines with bistrifluoromethyl pendant groups

Abstract: Fan-out Wafer-level Packaging (FOWLP) urgently demands low dielectric constant and dissipation factor interlayer dielectric materials to mitigate high transmission loss at high frequencies. Polyimides (PIs) are widely used as interlayer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The T g of these two PI films was collected using a comprehensive thermal analyzer (microcomputer differential thermal balance, HT-1) in an argon atmosphere with a flow rate of 50 mL min –1 , at a temperature increase of 10 °C min –1 . PI-6 to PI-10 were obtained from different recently published literature sources, each exhibiting significant structural variations. …”
Section: Methodsmentioning
confidence: 99%
“…The T g of these two PI films was collected using a comprehensive thermal analyzer (microcomputer differential thermal balance, HT-1) in an argon atmosphere with a flow rate of 50 mL min –1 , at a temperature increase of 10 °C min –1 . PI-6 to PI-10 were obtained from different recently published literature sources, each exhibiting significant structural variations. …”
Section: Methodsmentioning
confidence: 99%
“…They showed that the anisotropy and local chain rigidity of PI chains represented by DoP correlate to electrical energy loss rather than the dipole moment. Many studies about the dielectric properties of PIs, such as low- D k / D f PIs with cross-linking structures, long triphenyl side chains, and bulky bis­(trifluoromethyl) biphenyl pendant groups, have been reported to date. However, no quantitative analysis of the anisotropic dielectric properties of PI films based on theoretical principles has been reported using reproducible experimental methods with variable humidity measurements for systematic molecular design of low- D k / D f PI.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the density or polarizability are two effective strategies for minimizing the D k of PIs. It was demonstrated that introducing bulky fluorinated substituents into the backbone can significantly reduce the D k of PIs due to the strong electronegativity and low atomic polarizability of fluorine [ 19 , 20 ]. In addition, the introduction of fluorine endows PIs with good organo-solubility and lowers water absorption [ 21 ].…”
Section: Introductionmentioning
confidence: 99%